Transnacionalna kriminaliteta: Študijsko gradivo - Dobovšek, Bojan (2020)
Transnational crime: Study material. Book Transnational Crime outlines modern forms of crime in the light of hybrid threats. The most important organized criminal groups in the world are analyzed, starting with the Mafia to the Triads and the Yakuza. The following is a presentation of the basic activities of these groups, from the issue of drug and arms trafficking, to gambling and money laundering. Special emphasis is placed on the development of cyber organized crime and abuses in the financial world. This highlights the transition of criminal groups to the economy and their influence on politics. In order to have a clearer insight into the issue, the areas of human trafficking, crime related to works of art and the situation in the Western Balkans and in Slovenia are defined and analyzed in more detail.
Keywords: Organized crime; mafia; criminal groups; criminal activities; corruption